Cognitive function and brain activation before and after transcutaneous cervical vagus nerve stimulation in healthy adults: A concurrent tcVNS-fMRI study - Zhang, Han; Guo, Zhiwei; Qu, Yun; Zhao, Yu; Yang, Yuxuan; Du, Juan; Yang, Chunlan (Frontiers in Psychology, 2022)
Transcutaneous vagus nerve stimulation, which involves the application of electrical currents to the cervical (tcVNS) or auricular (taVNS) branches of the vagus nerve, may be a potential treatment for improving cognitive dysfunction. taVNS may improve cognitive performance in healthy adults, and fewer studies have been performed on the effects of tcVNS on cognition in healthy subjects. We conducted a randomized, single-blind, crossover-controlled trial to investigate the effects of tcVNS stimulation on cognitive function and neural activity in the brains of healthy adults. This study provides support for further tcVNS studies for the treatment of cognitive impairment. Twenty-one participants were randomly divided into two groups, A and B. Group A received tcVNS first and then sham-tcVNS, while group B received the intervention in the reverse order, receiving sham stimulation first and then true stimulation. All subjects were required to perform cognitive function tests before and after receiving intervention, and functional magnetic resonance imaging (fMRI) was performed concurrently during the intervention. We hypothesized that tcVNS would have an effect on the cognitive performance of the subjects and alter the neural activity of the brain. The present study showed that tcVNS had beneficial effects on cognitive performance, mainly improving memory and language skills and attention. tcVNS intervention produced significant spontaneous neural activity in the calcarine gyrus, fusiform gyrus, lingual gyrus, and parahippocampal gyrus of the brain. Future tcVNS/fMRI trials will need to explore the effects of changes in stimulus parameters on the neural activity response of the brain.